Words and Times. The Argentine Crisis of 2001 in Political Discourse (1999-2003) - Cané Pastorutti, Mariana (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2024)
This paper re-examines the Argentine crisis of 2001 by means of an analysis of discursive disputes over the “crisis” signifier in political discourse of the period 1999-2003. The theorical-methodological approach adopted articulates the post-foundational political thought and argumentative discourse analysis. As a result, we identify a process of disarticulation-rearticulation of the consensus on the possible and the desirable in connection with the diagnosis of the crisis (causes, scopes, solutions) and with the configuration of the time of the common (and this, in two levels: the one of the historical narrative, and that of the ontological time). Finally, we provide an interpretative key to account for the process of loss of legitimacy that the political word suffered in that period together with the antipolitical quality that characterizes the conception of time as inevitable.